FINANCIAL COMPENSATION, NON-PHYSICAL WORKING ENVIRONMENT, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE WORK SPIRIT - FAADILLAH ADHIRAJASA; KAREL TJAHJADI (Media Bisnis, 2021)
The purpose of this study is to see compensation compensation, non-physical work environment, and organizational commitment to employee morale. The research was conducted at PT Sorik Marapi Geothermal Power Jakarta. The number of samples taken was 70 employees, with the saturation / census sample method. Data were collected through a questionnaire. The analysis technique uses multiple linear regression analysis techniques. Initial observations found that PT Sorik Marapi Geothermal Power Jakarta had problems related to employee morale. This condition can be seen from the high level of employee absenteeism. Based on the analysis, it is known that financial compensation, non-physical work environment, and organizational commitment have a positive effect on employee morale. This shows that the higher the compensation and organizational commitment, the higher the employee morale. In an effort to increase the morale of employees of PT Sorik Marapi Geothermal Power Jakarta, the company must pay attention to indicators whose average value is below the average value.